HPV infection and P16 expression in oral and oropharyngeal cancer in Kazakhstan - Adilbay, Dauren; Adilbayev, Galim; Kidirbayeva, Gulzhan; Shipilova, Viktoria; Sadyk, Zhanat; Koyanbekova, Gulsum; Sokolenko, Ekaterina; Klozar, Jan (Infectious agents and cancer, 2018)
BACKGROUND: Human papillomavirus (HPV) is an important etiologic factor in different cancers of anogenital region and also in a fraction of head and neck cancers (HNC) particularly oropharyngeal tumors. The HPV16 genotype associated with the majority of HPV-related head and neck carcinomas. Th incidence of oropharyngeal cancer is increasing in many countries, and the rate of HPV positive tumors is about 70% in Europe and North America. Little known about the prevalence of HPV in HNC in Central Asia. METHODS: It's a prospective analysis of patients with verified oral or oropharyngeal cancer. Sociodemographic and clinical data obtained on admission to treatment. The diagnosis of HPV positivity assessed by both the P16 expression on immunohistochemistry(IHC) and polymerase chain reaction (PCR)with HPV DNA detection and HR HPV type determination. RESULTS: Seventy six patients with oral and oropharyngeal cancer tested for HPV. Forteen cases were positive for HPV by PCR and 15 cases by P16 IHC. Of the 35 oropharyngeal tumors, nine were HPV DNA and p16 IHC positive, giving the rate of 25.7%. Of the 41 oral tumors, five were HPV DNA and six p16 IHC positive, giving the rate of 12.2%. CONCLUSION: It is the first study mapping prevalence of HPV positivity in oral and oropharyngeal cancer in the Central Asian region. The rate of HPV positivity was higher in oropharyngeal than in oral cancer, the nonsmokers were significantly more frequent in the HPV positive group and HPV 16 was the most frequent type. However, the HPV positivity rates are lower than referred in the western world.
Keywords: This research was presented as an E-poster on IFOS 2017 ENT world congress (24–28 June) Paris, France. Abstract № HN-HPV-20.; Kazakhstan; HPV; Oropharyngeal cancer; Oral cavity; p16 IHC